Rational Choice and Its Limits - Towfigh, Emanuel V. (German law journal, 2016)
This Article asks the fundamental question of whether the concept of a market-oriented (economic) order can be reconciled with the idea of democracy from the perspective of rational choice approaches to the law. Europe has been facing great economic challenges for the past years—sovereign debt; fiscal and monetary policy; financial market regulation; trade and investment agreements. Some observers argue that prioritizing an economic rationale in the policy response to these challenges comes at the expense of democracy by undermining its most vital preconditions (such as equality and solidarity), while their antagonists state that in fact democratic decision-making is undermining financial stability and long-term welfare of societies. This Article will establish that both positions contribute important insights and yet display too narrow a field of vision. Combining the arguments puts the cart before the horse: Democratic decision-making undermines, among other things, financial stability—and thus long-term welfare of societies—because it follows a logic that is primarily economic.